Diagnosing and providing initial management for patients with Gestational Diabetes: What is the General Practitioner's experience?. (August 2020) - Green, Alison; Callaway, Leonie; McIntyre, H. David; Mitchell, Ben
Abstract: Aim: This study explores the General Practice (GP) experience of Gestational Diabetes Mellitus (GDM). Much has been written about patient perspectives, yet little is known about the GP perspective at initial diagnosis and management. GDM is increasingly managed in the secondary and tertiary sector, the confidence of GPs and their role in ongoing care has not been examined. Given GDM's poor follow up rates, all aspects of the patient journey warrant close examination. Methods: Through purposive and snowball sampling, we conducted semi-structured interviews with GPs in Brisbane, Australia between April and October 2018. Data collection, until saturation, and analysis were concurrent, and the Leximancer analysis tool assisted with content analysis and suggestion of themes. Results: Dominant themes include uncertainty/urgency and feeling under-utilised. GPs have a pragmatic approach in the face of uncertainty, and adopt one of several strategies to meet patient needs. A key issue that may impact on long term follow up and high quality GP-patient relationships is concern about the patient being 'taken away' by the hospital. Communication with the hospital is generally perceived as poor. Conclusions: The experience of GPs in the initial diagnosis and management of GDM may assist in improving GDM follow up.